Advertising to children new directions, new media - Blades, Mark (Palgrave Macmillan, 2014)
"This important source for students, researchers, advertisers and parents reviews the debates about advertising to children, and presents new information about children's understanding of advertising. Contributing authors analyse food and alcohol advertising and their effect on children and young people, and explore the point at which children can first identify advertisements and when they can understand that advertisements are persuasive messages. As well as reporting research about television advertising, this volume includes studies about advertising to children in new media, including web pages, search engines, and advergames. There is a discussion of the new ways that marketers reach children, for instance through the internet or with product placement, as well as practical explanations of how parents and educators can help children become more critical of advertisements"..